Observability of signatures of transport-induced chemistry in clear atmospheres of hot gas giant exoplanets. Issue 2 (24th November 2022) - Zamyatina, Maria; Hébrard, Eric; Drummond, Benjamin; Mayne, Nathan J; Manners, James; Christie, Duncan A; Tremblin, Pascal; Sing, David K; Kohary, Krisztian
ABSTRACT: Transport-induced quenching, i.e. the homogenization of chemical abundances by atmospheric advection, is thought to occur in the atmospheres of hot gas giant exoplanets. While some numerical modelling of this process exists, the three-dimensional nature of transport-induced quenching is underexplored. Here, we present results of 3D cloud- and haze-free simulations of the atmospheres of HAT-P-11b, HD 189733b, HD 209458b, and WASP-17b including coupled hydrodynamics, radiative transfer, and chemistry. Our simulations were performed with two chemical schemes: a chemical kinetics scheme, which is capable of capturing transport-induced quenching, and a simpler, more widely used chemical equilibrium scheme. We find that transport-induced quenching is predicted to occur in atmospheres of all planets in our sample; however, the extent to which it affects their synthetic spectra and phase curves varies from planet to planet. This implies that there is a 'sweet spot' for the observability of signatures of transport-induced quenching, which is controlled by the interplay between the dynamics and chemistry.